THE ISSUE OF LONELINESS IN THE PERIOD OF â€žEMERGING ADULTHOODâ€ - DomagaÅ‚a-Krecioch, Agnieszka; Majerek, Bozena (European Scientific Journal, ESJ, 2014)
Loneliness is a complex and multidimensional life experience affecting almost each individual. However, due to the turbulent social and civilization changes, it seems that a modern man more and more frequently suffers this unpleasant condition as well as emotions accompanying loneliness, that is: sadness, despair, apathy, diffidence, a sense of alienation. The phenomenon of loneliness has become a serious problem especially among the youth. This group indeed is subjected to intense and acute sense of loneliness, which is a result of, among others, low level of social skills, lack of emotional maturity or teachersâ€™ and parentsâ€™ insufficient interest in their problems. The proposed paper will present the most important theoretical and empirical standpoints, and analyze types and symptoms of loneliness among the youth. When discussing the causes and consequences of the phenomenon, the author refers to both Polish (e.g. Public Opinion Research Center) and European research reports (e.g. Mental Health Report, SUPRE, ESPAD). The speech will also demonstrate selected institutional forms of support for the youth who experience loneliness as well as other emotional and social problems.